Analisis Kualitas Laporan Keuangan Dalam Meningkatkan Transparansi Dan Akuntabilitas Organisasi - M. Andre Rivandy Siregar,; Sri Wardany, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The quality of financial reports plays a crucial role in supporting organizational transparency and accountability. However, in practice, various problems related to the preparation and presentation of financial reports still exist, resulting in low stakeholder trust. This study aims to analyze the concept, characteristics, and relationship between financial report quality and organizational transparency and accountability, based on previous research findings. The research method used was a literature review, examining national journal articles, reference books, and reports and regulations related to financial reporting. The literature was selected selectively based on topic suitability and publication recency. The analysis was conducted qualitatively using a descriptive-analytical approach. The results of the study indicate that the quality of financial reports, characterized by the relevance, reliability, clarity, and comparability of information, contributes significantly to the realization of organizational transparency. Furthermore, the quality of financial reports has a close and mutually reinforcing relationship with organizational accountability, whether in the context of government, the private sector, or non-profit organizations. Quality financial reports enable effective oversight and accountability processes and increase stakeholder trust. This study confirms that increasing organizational transparency and accountability does not.